The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1080/00420989650011537
|View full text |Cite
|
Sign up to set email alerts
|

Urban Economic Growth in Europe: Testing Theory and Policy Prescriptions

Abstract: A quite robust model of differential growth rates of per capita income in the major functional urban regions of the European Union is presented and tested for the 1980s. The results underline the important role of purely spatial economic processes in differential regional growth and suggest that the pattern of European urbanisation tends itself to generate systematic divergence of mean per capita incomes between neighbouring city-regions, even though the mechanism generating this divergence of mean incomes is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 20 publications
6
47
0
4
Order By: Relevance
“…Comparative studies are generally based on population indicators [6,9,32]. There are, however, numerous examples in which population and economic development do not necessarily go hand in hand.…”
Section: Measuring Shrinking Citiesmentioning
confidence: 99%
“…Comparative studies are generally based on population indicators [6,9,32]. There are, however, numerous examples in which population and economic development do not necessarily go hand in hand.…”
Section: Measuring Shrinking Citiesmentioning
confidence: 99%
“…An empirical analysis of urban growth in Europe was elaborated in Cheshire and Carbonaro (1996) and the model used is set out in the Appendix. For a number of reasons, variables that were likely to be important in at least some areas were not included.…”
Section: The Impact Of Territorial Competition On Local Growthmentioning
confidence: 99%
“…People might choose to live in the non-metro areas, which usually have a lower living cost, and commute to the metro areas in order to pursue a higher paying job (Partridge, Ali, & Olfert, 2010). Cheshire and Carbonaro (1996) showed that a strong positive relationship exists among the length of a commuting trip, income, and measures of human capital. Urban areas with higher income growth attract commuters from neighboring areas, thus increasing their workforce and total GDP.…”
Section: H2mentioning
confidence: 99%